The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.10.06.20207373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between white matter hyperintensity burden, cerebral blood flow and transit time in small vessel disease: an updated meta-analysis

Abstract: Cerebral small vessel disease is a major contributor to stroke and dementia, characterised by white matter hyperintensities (WMH) on neuroimaging. WMH are associated with reduced cerebral blood flow (CBF) cross-sectionally, though longitudinal associations remain unclear. We updated a 2016 meta-analysis, identifying 30 studies, 27 cross-sectional (n=2956) and 3 longitudinal (n=440), published since 2016. Cross-sectionally, we meta-analysed 10 new studies with 24 previously reported studies, total 34 (n=2180), … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
1
26
1
Order By: Relevance
“…12 Current databases. Articles from four recent systematic reviews [13][14][15][16] that met our inclusion criteria (see below) were included. These systematic reviews provided a large publication sample that had already been screened against objective criteria, quality assessed and conducted according to PRISMA standards (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Current databases. Articles from four recent systematic reviews [13][14][15][16] that met our inclusion criteria (see below) were included. These systematic reviews provided a large publication sample that had already been screened against objective criteria, quality assessed and conducted according to PRISMA standards (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…To explore the most recent research including participants with SVD, an independent database search was also carried out. The search strategy was modified from a published protocol 16 to identify studies including participants with clinical (stroke or cognitive presentations) or non-clinical presentations of sporadic or monogenic SVD (e.g. CADASIL) ischemi* or ischaemi* or silent or microscopic) adj3 lesion*).ti,ab.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence for low CBF predating SVD lesions in humans is limited. Cross-sectionally, patients with worse WMHs had lower resting CBF, but excluding studies with poorly age-matched controls and patients with dementia removed the association between WMHs and low CBF (63,64). Low CBF predates symptom onset in AD by several years (65) and separately predicts accelerated brain volume loss (66), potentially confounding studies of SVD and CBF.…”
Section: Observations From the Whole Human Perspective Vascular Risk ...mentioning
confidence: 99%
“…Of seven longitudinal studies of WMHs and CBF, the largest studies found that low baseline CBF did not predict worsening WMHs (64) but that worse baseline WMHs predicted falling CBF (67). Unfortunately, many studies did not account for vascular risk factors, exaggerating any apparent difference in CBF between the patients with WMHs and controls.…”
Section: Observations From the Whole Human Perspective Vascular Risk ...mentioning
confidence: 99%